LANGUAGE AND CULTURE RELATIONS AMONG SECOND LANGUAGE LEARNERS (European Journal of Interdisciplinary Research and Development, 2024)
This article explores the intricate relationship between language and culture among second language learners, emphasizing how cultural understanding influences language acquisition and communication. It examines the role of culture in shaping linguistic structures, expressions, and meanings, as well as its impact on the development of cross-cultural competence. By investigating the interconnectedness of language and culture, the study highlights the importance of integrating cultural knowledge into language learning curricula. Special attention is given to the challenges and opportunities faced by second language learners in navigating cultural nuances and fostering meaningful communication in a globalized world.